2022
DOI: 10.54680/fr22110110212
|View full text |Cite
|
Sign up to set email alerts
|

Cryoprotectant With A Mitochondrial Derived Peptide, Humanin, Improves Post-Thaw Quality Of Buffalo Spermatozoa

Abstract: BACKGROUND: Semen cryopreservation results in deleterious effects on spermatozoa, including lipid peroxidation and a reduction in the total antioxidant components of seminal plasma. The ultimate outcome of these changes is a reduction in post-thaw semen quality. A mitochondrial derived peptide, humanin, a potent cytoprotective and antioxidant agent was used in the present study. OBJECTIVE: To evaluate the efficacy of a mitochondrial-derived peptide, humanin to improve the post-thaw quality of buffalo spermato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Thus, the generation of ROS forms a vicious circle of self-generation and spermatozoal death; the greater the number of dead sperm, the greater the oxidative stress, which develops more cryoinjuries [31]. Previous studies from our laboratory have also reported a reduction in post-thaw sperm motility with the elevation of oxidative stress markers like malondialdehyde [32,33] and ROS [34,35].…”
Section: Discussionmentioning
confidence: 82%
“…Thus, the generation of ROS forms a vicious circle of self-generation and spermatozoal death; the greater the number of dead sperm, the greater the oxidative stress, which develops more cryoinjuries [31]. Previous studies from our laboratory have also reported a reduction in post-thaw sperm motility with the elevation of oxidative stress markers like malondialdehyde [32,33] and ROS [34,35].…”
Section: Discussionmentioning
confidence: 82%